A method for preparing a TiN / CrN composite electrode with high specific surface area

By depositing a metal Cr base layer and a CrN film transition layer with a columnar array structure on the substrate, a TiN/CrN composite electrode with a high specific surface area is formed, which solves the problem of poor binding force between the TiN film and the substrate, and improves the specific capacitance and cycle life.

CN119786282APending Publication Date: 2025-04-08XIAN SURFACE MATERIAL PROTECTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411984390.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The current TiN film has poor direct bonding force with the substrate, resulting in a large contact resistance, limiting the service life of the supercapacitor.

Method used

A mask is used to assist in depositing a metal Cr base layer with a columnar array structure on the substrate, and a CrN film is deposited on its surface as a transition layer, and finally a TiN film is deposited to form a TiN/CrN composite electrode with a high specific surface area.

Benefits of technology

By increasing the specific surface area of ​​the TiN/CrN composite electrode and improving the bonding force between the film and the substrate, the specific capacitance and cycle life are significantly improved and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786282A_ABST
    Figure CN119786282A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a TiN / CrN composite electrode with a high specific surface area, the method comprising: 1. etching the surface of a substrate; 2. after covering the etched substrate surface with a mask having a columnar array structure hole, introducing argon gas for deposition to form a metal Cr base layer with a columnar array structure; 3. introducing nitrogen and argon gas to deposit a CrN film on the surface of the metal Cr base layer; 4. introducing nitrogen and argon gas to deposit a TiN film on the CrN film transition layer to obtain a TiN / CrN composite electrode. The invention uses a mask to assist in first depositing a metal Cr base layer with a columnar array structure on the substrate, and then depositing a CrN film as a transition layer, thereby effectively increasing the specific surface area of ​​the TiN / CrN composite electrode, improving the specific capacitance of the TiN film, and enhancing the bonding force between the TiN film and the substrate, thereby greatly improving the specific capacitance and cycle life of the TiN / CrN composite electrode, and is suitable for the field of supercapacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of supercapacitor energy storage, and in particular relates to a method for preparing a TiN / CrN composite electrode with a high specific surface area. Background Art

[0002] Supercapacitors are a new type of energy storage device between batteries and traditional electrostatic capacitors, which can make up for the low energy density of traditional capacitors and the low power density of batteries. Due to their good temperature characteristics, high specific capacitance, high energy density and power density, short charging time, long service life, energy saving and environmental protection, they are widely used in aerospace, electronic products, portable power supplies, electric vehicles and other fields.

[0003] Transition metal nitrides have the advantages of pseudocapacitive properties, good electrical conductivity and stable cycle stability, and are often used as electrode materials for supercapacitors. Nitride electrode materials are often obtained by direct nitridation of single substances. However, during the carbon thermal reduction process of nitrides prepared by chemical vapor deposition, the temperature is too high and the oxygen content on the nitride surface cannot be controlled, resulting in a slow nitride deposition rate and the release of toxic gases. The nitride film obtained by physical vapor deposition has the characteristics of fast deposition rate and controllable thickness.

[0004] TiN among transition metal nitrides has excellent physical and chemical properties such as high melting point, high hardness and oxidation resistance. Arc ion plating is often used to deposit TiN thin film on the surface of stainless steel. By changing the process parameters of TiN thin film deposition such as deposition temperature, nitrogen flow rate and deposition time, the resistivity of TiN thin film can be controlled from tens to thousands of μΩ·cm. The obtained TiN thin film can be used as an electron transport collector to connect the charge and discharge circuit, and can also be used as a high pseudocapacitor electrode to store charge. However, when TiN thin film is deposited on the surface of 304 stainless steel using physical vapor deposition, since stainless steel and TiN thin film are different types of materials, the lattice adaptation and thermal expansion coefficient differences will cause the direct bonding between TiN thin film and substrate to be poor, and at the same time lead to a large contact resistance of TiN electrode. These problems seriously limit the service life of supercapacitors. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a TiN / CrN composite electrode with a high specific surface area in view of the deficiencies of the above-mentioned prior art. The method first deposits a metal Cr base layer of a columnar array structure on a substrate with the assistance of a mask, and then deposits a CrN film as a transition layer on the metal Cr base layer, which effectively increases the specific surface area of ​​the TiN / CrN composite electrode, improves the specific capacitance of the TiN film, and enhances the bonding force between the TiN film and the substrate, thereby greatly improving the specific capacitance and cycle life of the TiN / CrN composite electrode, and solving the problem that the direct bonding force between the TiN film and the substrate is poor and the contact resistance is large, which affects the application.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a TiN / CrN composite electrode with a high specific surface area, characterized in that the method comprises the following steps:

[0007] Step 1, heating the furnace chamber of the arc ion plating equipment, then introducing argon gas into the furnace chamber and heating it, then introducing hydrogen gas into the furnace chamber and heating it, etching the surface of the substrate, and stopping introducing gas into the furnace chamber after etching is completed, and removing the remaining hydrogen in the furnace chamber;

[0008] Step 2: A mask having a columnar array structure hole is covered on the substrate surface after being etched in step 1, and then argon gas is introduced into the furnace chamber after the hydrogen is removed in step 1, and deposition is performed on the substrate surface covered with the mask. After the deposition is completed, the mask is removed to form a metal Cr base layer with a columnar array structure on the substrate surface;

[0009] Step 3, nitrogen and argon are introduced into the furnace chamber, and then a CrN film is deposited on the surface of the metal Cr base layer of the columnar array structure formed on the surface of the substrate in step 2;

[0010] Step 4: nitrogen and argon are introduced into the furnace chamber, and then a TiN film is deposited on the CrN film transition layer deposited in step 3 to obtain a TiN / CrN composite electrode.

[0011] The present invention firstly deposits a metal Cr base layer of a columnar array structure on the surface of a substrate with the assistance of a mask template. The columnar array structure is used to increase the specific surface area of ​​the interface and thus the specific surface area of ​​the TiN / CrN composite electrode, thereby promoting the TiN / CrN composite electrode to have more charge storage during the charge and discharge process, thereby improving the specific capacitance of the TiN film. On the other hand, more nucleation sites are provided for subsequent film deposition, thereby improving the deposition rate of the film. At the same time, a mutually interlocking structure is formed between the film and the substrate, thereby improving the bonding strength between the film and the substrate, and enhancing the cycle stability of the TiN / CrN composite electrode during the charging process. Secondly, the present invention deposits a CrN film as a transition layer on the surface of the metal Cr base layer of the columnar array structure formed on the surface of the substrate, and utilizes the characteristics of the CrN film and the metal Cr base layer having the same element Cr, so that the CrN film and the metal Cr base layer are well bonded. At the same time, since the thermal expansion coefficients of the CrN film and the TiN film are close, the two are also well bonded, thereby enhancing the bonding force between the TiN film and the substrate and reducing the contact resistance of the TiN film. In addition, CrN has higher electrical conductivity and corrosion resistance, while TiN has better pseudocapacitance. The TiN / CrN composite electrode prepared on the surface of the substrate with the TiN film coated with the CrN film can play the synergistic effect of the two nitrides, so that the TiN / CrN composite electrode has excellent electrical conductivity and pseudocapacitance.

[0012] The above-mentioned method for preparing a high specific surface area TiN / CrN composite electrode is characterized in that in step one, the furnace chamber is heated to 460°C and maintained for 20 minutes so that the background vacuum does not exceed 4.0×10-3Pa, and then argon gas is introduced into the furnace chamber at a flow rate of 200sccm, and the temperature is raised to 400°C~450°C for heating. When the vacuum degree of the furnace chamber does not exceed 5.0×10-1Pa, hydrogen gas is introduced into the furnace chamber, and the flow rate of hydrogen gas is 100sccm~150sccm, while the flow rate of argon gas is 150sccm~200sccm, and the temperature is raised to 550°C~600°C for heating, and the etching time is 30min~60min.

[0013] The above-mentioned method for preparing a TiN / CrN composite electrode with a high specific surface area is characterized in that the diameter of the columnar array structure holes on the mask template in step 2 is 100 μm, and the hole edge spacing between adjacent holes is 50 μm.

[0014] The above-mentioned method for preparing a high specific surface area TiN / CrN composite electrode is characterized in that the flow rate of the argon gas introduced in step 2 is 150sccm~200sccm, and the vacuum degree of the argon gas introduced into the furnace chamber is 5.0×10-1Pa, the deposition temperature is 400℃~450℃, the bias voltage is 100V~150V, and the deposition time is 10min~20min.

[0015] The above-mentioned method for preparing a high specific surface area TiN / CrN composite electrode is characterized in that the flow rates of nitrogen and argon introduced in step three are 600sccm~800sccm and 300sccm~400sccm respectively, and the vacuum degree of the furnace chamber when nitrogen and argon are introduced is 0.5Pa~1.5Pa, the temperature of depositing the CrN film is 400℃~500℃, the bias voltage is 0V, and the deposition time is 10min~40min.

[0016] The above-mentioned method for preparing a high specific surface area TiN / CrN composite electrode is characterized in that the thickness of the CrN film in step three is 300nm to 500nm.

[0017] The above-mentioned method for preparing a high specific surface area TiN / CrN composite electrode is characterized in that the flow rates of nitrogen and argon introduced in step 4 are 700sccm~900sccm and 80sccm~120sccm respectively, and the vacuum degree of the furnace chamber when nitrogen and argon are introduced is 0.5Pa~1.5Pa, the temperature of depositing the TiN film is 400℃~500℃, the bias voltage is 0V, and the deposition time does not exceed 50min.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The present invention adopts an arc ion plating method to first deposit a metal Cr base layer with a columnar array structure on a substrate, and then deposit a CrN thin film transition layer and a TiN thin film. The columnar array structure is used to increase the specific surface area of ​​the interface, thereby effectively increasing the specific surface area of ​​the TiN / CrN composite electrode, improving the specific capacitance of the TiN film, and forming a mutual interlocking structure between the film and the substrate, thereby improving the bonding strength between the film and the substrate and enhancing the charging cycle stability of the TiN / CrN composite electrode.

[0020] 2. The present invention deposits a CrN film as a transition layer on the metal Cr base layer of the columnar array structure, so that the CrN film is well bonded with the metal Cr base layer and the TiN film, thereby enhancing the bonding force between the TiN film and the substrate, reducing the contact resistance of the TiN film, and extending the service life of the TiN / CrN composite electrode.

[0021] 3. The present invention controls the thickness of the CrN film and adjusts the deposition time of the TiN film to achieve thickness matching between the TiN film and the CrN film, thereby obtaining a TiN / CrN composite electrode with optimal supercapacitor performance.

[0022] 4. The present invention prepares a TiN / CrN composite electrode in which a TiN film is coated with a CrN film on the surface of a substrate, giving full play to the synergistic effect of the higher conductivity and corrosion resistance of CrN and the better pseudocapacitance of TiN, so that the TiN / CrN composite electrode has excellent conductivity and pseudocapacitance.

[0023] 5. The present invention enhances the bonding force between the film and the substrate by designing the interface structure between the substrate and the film and depositing the TiN / CrN composite electrode, thereby greatly improving the specific capacitance and cycle life of the TiN / CrN composite electrode. According to electrochemical analysis, the capacitance retention rate of the TiN / CrN composite electrode is still 95.8% after 20,000 cycles.

[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the surface morphology of the metal Cr base layer that forms a columnar array structure on the substrate surface in the present invention.

[0026] Figure 2 It is a schematic diagram of the three-dimensional morphology of the metal Cr base layer that forms a columnar array structure on the surface of the substrate in the present invention.

[0027] Figure 3 This is a comparison of the surface micromorphologies of the TiN / CrN composite electrodes prepared in Example 7 of the present invention and in Comparative Example 1.

[0028] Figure 4 1 is a charge-discharge cycle diagram of the TiN / CrN composite electrode prepared with different TiN film deposition times in Examples 7 to 9 of the present invention. DETAILED DESCRIPTION

[0029] Example 1

[0030] This embodiment includes the following steps:

[0031] Step 1: Use metal cleaning agent, anhydrous ethanol and deionized water to clean the substrate for 20 minutes, 15 minutes and 10 minutes respectively, and use a hair dryer to dry it after taking it out;

[0032] The dried substrate was placed in the furnace chamber of the arc ion plating equipment, and the dried substrate was cleaned for 20 minutes using an anode ion source. During the cleaning, the pressure in the furnace chamber was 0.1 Pa, the argon gas flow rate was 120 sccm, and the substrate bias voltage was 40 V.

[0033] The furnace chamber of the arc ion plating equipment was heated to 460°C for 20 min to ensure that the background vacuum did not exceed 4.0×10 -3 Pa, then argon gas is introduced into the furnace chamber at a flow rate of 200 sccm and the temperature is raised to 400°C for heating, and hydrogen gas is introduced into the furnace chamber at a flow rate of 100 sccm and the temperature is raised to 550°C for heating, and the flow rate of argon gas introduced at the same time is 150 sccm, and the cleaned substrate surface is etched for 30 minutes. After the etching is completed, the gas introduction into the furnace chamber is stopped, and the remaining hydrogen in the furnace chamber is removed;

[0034] Step 2: A mask having columnar array structure holes is placed on the surface of the substrate after being etched in step 1, and then argon gas with a flow rate of 150 sccm is introduced into the furnace chamber after hydrogen is removed in step 1 until the vacuum degree of the furnace chamber reaches 5.0×10 - 1 Pa is deposited on the substrate surface covered with a mask, the deposition temperature is 400°C, the bias voltage is 100V, and the deposition time is 10min. After the deposition is completed, the mask is removed to form a metal Cr bottom layer with a columnar array structure on the substrate surface. The schematic diagram is shown in Figure 1 and Figure 2 As shown;

[0035] Step 3, nitrogen and argon are introduced into the furnace chamber with flow rates of 600 sccm and 300 sccm respectively until the vacuum degree of the furnace chamber is 0.5 Pa, and then a CrN film with a thickness of 300 nm is deposited on the surface of the metal Cr base layer of the columnar array structure formed on the surface of the substrate in step 2, the deposition temperature is 400°C, the bias voltage is 0V, and the deposition time is 10 min;

[0036] Step 4: Nitrogen and argon are introduced into the furnace chamber with flow rates of 700 sccm and 80 sccm respectively until the vacuum degree of the furnace chamber is 0.5 Pa, and then a TiN film is deposited on the CrN film transition layer deposited in step 3. The deposition temperature is 400°C, the bias voltage is 0 V, and the deposition time is 10 min to obtain a TiN / CrN composite electrode.

[0037] Example 2

[0038] The difference between this embodiment and embodiment 1 is that the time for depositing the TiN film in step 4 is 30 minutes.

[0039] Example 3

[0040] The difference between this embodiment and embodiment 1 is that the time for depositing the TiN film in step 4 is 50 minutes.

[0041] Example 4

[0042] This embodiment includes the following steps:

[0043] Step 1: Use metal cleaning agent, anhydrous ethanol and deionized water to clean the substrate for 20 minutes, 15 minutes and 10 minutes respectively, and use a hair dryer to dry it after taking it out;

[0044] The dried substrate was placed in the furnace chamber of the arc ion plating equipment, and the dried substrate was cleaned for 20 minutes using an anode ion source. During the cleaning, the pressure in the furnace chamber was 0.1 Pa, the argon gas flow rate was 120 sccm, and the substrate bias voltage was 40 V.

[0045] The furnace chamber of the arc ion plating equipment was heated to 460°C for 20 min to ensure that the background vacuum did not exceed 4.0×10 -3 Pa, then argon gas is introduced into the furnace chamber at a flow rate of 200 sccm and the temperature is raised to 450°C for heating, and hydrogen gas is introduced into the furnace chamber at a flow rate of 150 sccm and the temperature is raised to 600°C for heating, and the flow rate of argon gas introduced is 200 sccm, and the cleaned substrate surface is etched for 60 minutes. After the etching is completed, the gas introduction into the furnace chamber is stopped, and the remaining hydrogen in the furnace chamber is removed;

[0046] Step 2: A mask having columnar array structure holes is placed on the surface of the substrate after etching in step 1, and then argon gas with a flow rate of 200 sccm is introduced into the furnace chamber after hydrogen is removed in step 1 until the vacuum degree of the furnace chamber reaches 5.0×10 - 1 Pa is deposited on the substrate surface covered with a mask, the deposition temperature is 450°C, the bias voltage is 150V, and the deposition time is 20min. After the deposition is completed, the mask is removed to form a metal Cr bottom layer with a columnar array structure on the substrate surface. The schematic diagram is shown in Figure 1 and Figure 2 As shown;

[0047] Step 3, nitrogen and argon are introduced into the furnace chamber with flow rates of 800 sccm and 400 sccm respectively until the vacuum degree of the furnace chamber is 1.5 Pa, and then a CrN film with a thickness of 500 nm is deposited on the surface of the metal Cr base layer of the columnar array structure formed on the surface of the substrate in step 2, the deposition temperature is 500°C, the bias voltage is 0V, and the deposition time is 40min;

[0048] Step 4: Nitrogen and argon are introduced into the furnace chamber with flow rates of 900 sccm and 120 sccm respectively until the vacuum degree of the furnace chamber is 1.5 Pa, and then a TiN film is deposited on the CrN film transition layer deposited in step 3. The deposition temperature is 500°C, the bias voltage is 0 V, and the deposition time is 10 min to obtain a TiN / CrN composite electrode.

[0049] Example 5

[0050] The difference between this embodiment and embodiment 4 is that the time for depositing the TiN film in step 4 is 30 minutes.

[0051] Example 6

[0052] The difference between this embodiment and embodiment 4 is that the time for depositing the TiN film in step 4 is 50 minutes.

[0053] Example 7

[0054] This embodiment includes the following steps:

[0055] Step 1: Use metal cleaning agent, anhydrous ethanol and deionized water to clean the substrate for 20 minutes, 15 minutes and 10 minutes respectively, and use a hair dryer to dry it after taking it out;

[0056] The dried substrate was placed in the furnace chamber of the arc ion plating equipment, and the dried substrate was cleaned for 20 minutes using an anode ion source. During the cleaning, the pressure in the furnace chamber was 0.1 Pa, the argon gas flow rate was 120 sccm, and the substrate bias voltage was 40 V.

[0057] The furnace chamber of the arc ion plating equipment was heated to 460°C for 20 min to ensure that the background vacuum did not exceed 4.0×10 -3 Pa, then argon gas is introduced into the furnace chamber at a flow rate of 200 sccm and the temperature is raised to 440°C for heating, and hydrogen gas is introduced into the furnace chamber at a flow rate of 125 sccm and the temperature is raised to 570°C for heating, and the flow rate of argon gas introduced at the same time is 160 sccm, and the surface of the cleaned substrate is etched for 50 minutes. After the etching is completed, the gas introduction into the furnace chamber is stopped, and the remaining hydrogen in the furnace chamber is removed;

[0058] Step 2: A mask having columnar array structure holes is placed on the surface of the substrate after being etched in step 1, and then argon gas with a flow rate of 180 sccm is introduced into the furnace chamber after hydrogen is removed in step 1 until the vacuum degree of the furnace chamber reaches 5.0×10 - 1Pa, deposited on the surface of the substrate covered with a mask, the deposition temperature was 440°C, the bias voltage was 120V, the deposition time was 15min, the mask was removed after the deposition was completed, and a metal Cr base layer of a columnar array structure was formed on the surface of the substrate; the aperture of the columnar array structure holes on the mask was 100μm, and the hole edge spacing between adjacent holes was 50μm;

[0059] Step 3, nitrogen and argon are introduced into the furnace chamber with flow rates of 700 sccm and 350 sccm respectively until the vacuum degree of the furnace chamber is 1.45 Pa, and then a CrN film with a thickness of 350 nm is deposited on the surface of the metal Cr base layer of the columnar array structure formed on the surface of the substrate in step 2, the deposition temperature is 450°C, the bias voltage is 0V, and the deposition time is 30min;

[0060] Step 4: Nitrogen and argon are introduced into the furnace chamber with flow rates of 800 sccm and 100 sccm respectively until the vacuum degree of the furnace chamber is 1.45 Pa, and then a TiN film is deposited on the CrN film transition layer deposited in step 3. The deposition temperature is 450°C, the bias voltage is 0 V, and the deposition time is 10 min to obtain a TiN / CrN composite electrode.

[0061] Example 8

[0062] The difference between this embodiment and embodiment 7 is that the time for depositing the TiN film in step 4 is 30 minutes.

[0063] Example 9

[0064] The difference between this embodiment and embodiment 7 is that the time for depositing the TiN film in step 4 is 50 minutes.

[0065] Comparative Example 1

[0066] The difference between this comparative example and Example 7 is that step 2 is not performed, and CrN film and TiN film are directly deposited on the surface of the substrate through steps 3 and 4.

[0067] Figure 3 Surface microscopic morphology comparison diagram of the TiN / CrN composite electrode prepared in Example 7 of the present invention and in Comparative Example 1, wherein Figure (a) represents the TiN / CrN composite electrode formed in Example 7 on a substrate having a metal Cr bottom layer with a columnar array structure, and Figure (b) represents the TiN / CrN composite electrode formed in Comparative Example 1 on a substrate without a columnar array structure. Figure 3 Combination Figure 1-2 It can be seen that the present invention significantly increases the specific surface area of ​​the TiN / CrN composite electrode by pre-depositing a metal Cr base layer having a columnar array structure on the substrate.

[0068] Figure 4The charge-discharge cycle diagram of the TiN / CrN composite electrode prepared by using different TiN film deposition times in Examples 7 to 9 of the present invention is shown in FIG. Figure 4 It can be seen that the capacitance retention rates of the TiN / CrN composite electrodes prepared in Examples 7 to 9 after 20,000 cycles are 93.3%, 95.8% and 92.5%, respectively, among which the TiN / CrN composite electrode prepared with a TiN film deposition time of 30 min in Example 2 has the best cycle life.

[0069] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a high specific surface area TiN / CrN composite electrode, characterized in that: The method comprises the following steps: Step 1, heating the furnace chamber of the arc ion plating equipment, then introducing argon gas into the furnace chamber and heating it, then introducing hydrogen gas into the furnace chamber and heating it, etching the surface of the substrate, and stopping introducing gas into the furnace chamber after etching is completed, and removing the remaining hydrogen in the furnace chamber; Step 2: A mask having a columnar array structure hole is covered on the substrate surface after being etched in step 1, and then argon gas is introduced into the furnace chamber after the hydrogen is removed in step 1, and deposition is performed on the substrate surface covered with the mask. After the deposition is completed, the mask is removed to form a metal Cr base layer with a columnar array structure on the substrate surface; Step 3, nitrogen and argon are introduced into the furnace chamber, and then a CrN film is deposited on the surface of the metal Cr base layer of the columnar array structure formed on the surface of the substrate in step 2; Step 4: nitrogen and argon are introduced into the furnace chamber, and then a TiN film is deposited on the CrN film transition layer deposited in step 3 to obtain a TiN / CrN composite electrode.

2. The method for preparing a high specific surface area TiN / CrN composite electrode according to claim 1, characterized in that: In step 1, the furnace chamber is heated to 460°C for 20 min so that the background vacuum does not exceed 4.0×10 -3 Pa, then argon gas is introduced into the furnace at a flow rate of 200 sccm, and the temperature is raised to 400℃~450℃ for heating. When the vacuum degree of the furnace chamber does not exceed 5.0×10 -1 Pa, hydrogen is introduced into the furnace chamber, and the flow rate of the hydrogen is 100sccm-150sccm, and the flow rate of argon is 150sccm-200sccm, and the temperature is raised to 550℃-600℃ for heating, and the etching time is 30min-60min.

3. The method for preparing a high specific surface area TiN / CrN composite electrode according to claim 1, characterized in that: In step 2, the diameter of the holes in the columnar array structure on the mask is 100 μm, and the spacing between the edges of adjacent holes is 50 μm.

4. The method for preparing a high specific surface area TiN / CrN composite electrode according to claim 1, characterized in that: The flow rate of the argon gas introduced in step 2 is 150 sccm to 200 sccm, and the vacuum degree of the furnace chamber is 5.0×10 -1 Pa, the deposition temperature is 400° C. to 450° C., the bias voltage is 100 V to 150 V, and the deposition time is 10 min to 20 min.

5. The method for preparing a high specific surface area TiN / CrN composite electrode according to claim 1, characterized in that: In step three, the flow rates of nitrogen and argon are 600 sccm to 800 sccm and 300 sccm to 400 sccm respectively, and the vacuum degree of the furnace chamber is 0.5 Pa to 1.5 Pa. The temperature of depositing the CrN film is 400°C to 500°C, the bias voltage is 0V, and the deposition time is 10min to 40min.

6. The method for preparing a high specific surface area TiN / CrN composite electrode according to claim 1, characterized in that: The thickness of the CrN film in step 3 is 300nm-500nm.

7. The method for preparing a high specific surface area TiN / CrN composite electrode according to claim 1, characterized in that: In step 4, the flow rates of nitrogen and argon are 700 sccm to 900 sccm and 80 sccm to 120 sccm respectively, and the vacuum degree of the furnace chamber is 0.5 Pa to 1.5 Pa. The temperature of depositing the TiN film is 400°C to 500°C, the bias voltage is 0V, and the deposition time does not exceed 50 minutes.